THE INFLUENCE OF COST-FACIT AND HEALTH-RELATED QUALITY OF LIFE IN CANCER PATIENTS: A NARRATIVE REVIEW - Wulandari, Aprilla Ayu; Andayani, Tri Murti; Endarti, Dwi; Pratiwi, Woro Rukmi (Universitas Muhammadiyah Magelang, 2025)
COST-FACIT is a financial toxicity measurement instrument that has been validated in several countries. Financial toxicity is a broad term that includes the costs a patient has to bear after a cancer diagnosis, which impacts personal and family budgets. This has implications for increasing awareness of the financial toxicity experienced by cancer patients so that it can support better policies and funding decisions by hospital management and the government. This article is a Narrative Review on studies regarding the influence of COST-FACIT and HRQoL in cancer patients. Search for English articles using the Pubmed, ScienceDirect, and Google Scholar databases, which were published from 2012 to 2022. Based on the Narrative Review that has been done, there are 19 articles that meet the criteria. In the article there are various HRQoL dimensions that are correlated with COST-FACIT. Dimensions that have a moderate to strong influence are psychological (emotional) and financial because the occurrence of financial toxicity can disrupt family expenses every month. If this continues, it can result in psychological distress for the patients and their family.